Holocene vegetation, fire and climate interactions on the westernmost fringe of the Mediterranean Basin - Morales-Molino, César; García-Antón, Mercedes; Postigo-Mijarra, José M; Morla, Carlos (Quaternary Science Reviews, 2013)
A new palaeoecological sequence from the western Iberian Central Range signiﬁcantly contributes to the knowledge on the Holocene vegetation dynamics in central Iberia. This sequence supports the existence of time-transgressive changes in the vegetation cover during the beginning of the Holocene over these central Iberian mountains, speciﬁcally the replacement of boreal birchepine forests with Mediterranean communities. Anthracological analyses also indicate the replacement of boreal pines (Pinus sylvestris) with Mediterranean ones (Pinus pinaster) during the early Holocene. The observed vegetation changes were generally synchronous with climatic phases previously reconstructed for the western Mediterranean region, and they suggest that the climatic trends were most similar to those recorded in the northern Mediterranean region and central Europe. Several cycles of secondary succession after ﬁre ending with the recovery of mature forest have been identiﬁed, which demonstrates that the vegetation of western Iberia was highly resilient to ﬁre disturbance. However, when the recurrence of ﬁre crossed a certain threshold, the original forests were not able to completely recover and shrublands and grasslands became dominant; this occurred approximately 5800e5400 cal yr BP. Afterwards, heathlands established as the dominant vegetation, which were maintained by frequent and severe wildﬁres most likely associated with human activities in a climatic framework that was less suitable for temperate trees. Finally, our palaeoecological record provides guidelines on how to manage protected areas in Mediterranean mountains of southwestern Europe, especially regarding the conservation and restoration of temperate communities that are threatened there such as birch stands.
Keywords: Betula; charcoal; Fire ecology; Forest management; Heathlands; macrofossils; pollen; Spain

Holocene vegetation and fire dynamics in the supra-mediterranean belt of the Nebrodi Mountains (Sicily, Italy) - Bisculm, Martina; Colombaroli, Daniele; Vescovi, Elisa; van Leeuwen, Jacqueline F. N.; Henne, Paul D.; Rothen, Julian; Procacci, Giovanni; Pasta, Salvatore; La Mantia, Tommaso; Tinner, Willy (Journal of Quaternary Science, 2012)
High-resolution pollen, macrofossil and charcoal data, combined with accelerator mass spectrometry 14C dating and multivariate analysis, were used to reconstruct Holocene vegetation and fire dynamics at Urio Quattrocchi, a small lake in the supra-mediterranean belt in the Nebrodi Mountains of Sicily (Italy). The data suggest that after 10 000 cal a BP increasing moisture availability supported closed forests with deciduous (Quercus cerris, Fagus sylvatica and Fraxinus spp.) and evergreen (Quercus ilex) species. Species-rich closed forest persisted until 6850 cal a BP, when Neolithic activities caused a forest decline and affected plant diversity. Secondary forest with abundant Ilex aquifolium recovered between 6650 and 6000 cal a BP, indicating moist conditions. From 5000 cal a BP, agriculture and pastoralism led to the currently fragmented landscape with sparse deciduous forests (Quercus cerris). The study suggests that evergreen broadleaved species were more important at elevations above 1000 m a.s.l. before ca. 5000 cal a BP than subsequently, which might reflect less human impact or warmer-than-today climatic conditions between 10 000 and 5000 cal a BP. Despite land use since Neolithic times, deciduous supra-mediterranean forests were never completely displaced from the Nebrodi Mountains, because of favourable moist conditions that persisted throughout the Holocene. Reconstructed vegetation dynamics document the absence of any pronounced mid- or late-Holocene ‘aridification’ trend at the site, an issue which is controversially debated in Italy and the Mediterranean region. Copyright © 2012 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: climate change; human impact; Ilex aquifolium; macrofossils; pollen; Quercus ilex